Inbreeding depression in crambe1 - Lara-fioreze, Ana Carolina Da Costa; Pivetta, Laerte Gustavo; Zanotto, Maurício Dutra (Escola de Agronomia/UFG, 2016)
ABSTRACT Inbreeding depression in plants, caused by selfing or crossing among plants with a high degree of relatedness, is a genetic phenomenon that affects quantitative traits. This study aimed at verifying the occurrence of inbreeding depression in crambe progenies originated from selfing, in comparison with open pollination progenies. A randomized blocks design, with three replications, in a 32 x 2 factorial arrangement, with 32 crambe progenies and two reproduction systems (artificial selfing and open pollination), was used. Grain yield, 1,000-grain weight, plant height and final stand were evaluated. A significant interaction was observed between progenies and reproduction systems in all traits evaluated. A reduction in grain yield, 1,000-grain weight and plant height occurred in the majority of the selfing progenies, when compared to open pollination progenies. Inbreeding depression was observed in all traits, especially for grain yield. The heritability coefficients of selfed progenies were higher than the open pollinated ones, except for 1,000-grain weight.

RESUMO A depressão por endogamia em plantas, causada por autofecundação ou cruzamento entre plantas com alto grau de parentesco, é um fenômeno genético que afeta os caracteres quantitativos. Objetivou-se verificar a ocorrência de depressão por endogamia em progênies de crambe originadas de autofecundação, em comparação com progênies de polinização livre. O delineamento experimental foi em blocos casualizados, com três repetições, em esquema fatorial 32 x 2, em que foram avaliadas 32 progênies de crambe sob dois sistemas de reprodução (autofecundação artificial e polinização livre). Foram avaliados a produtividade de grãos, massa de 1.000 grãos, altura de planta e estande final. Observou-se interação significativa entre progênies e sistemas de reprodução para todas as características avaliadas. Para a maioria das progênies, houve redução na produtividade de grãos, massa de 1.000 grãos e altura de plantas oriundas de autofecundação, em comparação com as progênies de polinização livre. Houve depressão por endogamia para todas as características avaliadas, especialmente para a produtividade de grãos. Os coeficientes de herdabilidade para as progênies oriundas de autofecundação foram maiores do que para as de polinização livre, exceto para massa de 1.000 grãos.
Depressão por endogamia em crambe
Keywords: Crambe abyssinica Hochst; selfing; open pollination; heritability; Crambe abyssinica Hochst; autofecundação; polinização aberta; herdabilidade